PENGELOLAAN SAMPAH ORGANIK DI SD YPK III BETEL, KELURAHAN DOOM BARAT DISTRIK SORONG KEPULAUAN KOTA SORONG - Leiwakabessy, Ivonne; Penda, Joni; Pairunan, Frederik; Gultom, Dormauli Br (SOLIDEO Jurnal Pengabdian Masyarakat, 2024)
Organic waste is waste originated/composed of living matter, such as weathering the remains of plants, animals, and humans. Biomass waste which if treated properly can be used as compost for plant fertilizer. This community service activity aims to provide knowledge related to the potential of natural resources or organic waste as material for making organic fertilizer. Compost making training. Training was provided for students of SD YPK III Bethel Doom by providing organic waste material and how to make organic compost. The results of this community service activity provide knowledge from SD YPK III Bethel Doom about the use of organic waste / waste in the surrounding environment increases and students can make compost organic fertilizer by utilizing biomass around school and residential environments